Mouse pulmonary dose- and time course-responses induced by exposure to nitrogen-doped multi-walled carbon nanotubes. (2nd January 2020) - Porter, Dale W.; Orandle, Marlene; Zheng, Peng; Wu, Nianqiang; Hamilton, Raymond F.; Holian, Andrij; Chen, Bean T.; Andrew, Michael; Wolfarth, Michael G.; Battelli, Lori; Tsuruoka, Shuji; Terrones, Mauricio; et al.
Abstract: Objective: In this study, we compared in vitro and in vivo bioactivity of nitrogen-doped multi-walled carbon nanotubes (NDMWCNT) to MWCNT to test the hypothesis that nitrogen doping would alter bioactivity. Materials and Methods: High-resolution transmission electron microscopy (TEM) confirmed the multilayer structure of MWCNT with an average layer distance of 0.36 nm, which was not altered by nitrogen doping: the nanomaterials had similar widths and lengths. In vitro studies with THP-1 cells and alveolar macrophages from C57BL/6 mice demonstrated that NDMWCNT were less cytotoxic and stimulated less IL-1β release compared to MWCNT. For in vivo studies, male C57BL/6J mice received a single dose of dispersion medium (DM), 2.5, 10 or 40 µg/mouse of NDMWCNT, or 40 µg/mouse of MWCNT by oropharyngeal aspiration. Animals were euthanized between 1 and 7 days post-exposure for whole lung lavage (WLL) studies. Results and Discussion: NDMWCNT caused time- and dose-dependent pulmonary inflammation. However, it was less than that caused by MWCNT. Activation of the NLRP3 inflammasome was assessed in particle-exposed mice by determining cytokine production in WLL fluid at 1 day post-exposure. Compared to DM-exposed mice, IL-1β and IL-18 were significantly increased in MWCNT- and NDMWCNT-exposed mice, but the increase caused by NDMWCNT was less than MWCNT. At 56 days post-exposure, histopathology determined lung fibrosis in MWCNT-exposed mice was greater than NDMWCNT-exposed mice. Conclusions: These data indicate nitrogen doping of MWCNT decreases their bioactivity, as reflected with lower in vitro and in vivo toxicity inflammation and lung disease. The lower activation of the NLRP3 inflammasome may be responsible. Abbreviations: NDMWCNT: nitrogen-doped multi-walled carbon nanotubes; MWCNT: multi-walled carbon nanotubes; TEM: transmission electron microscopy; HRTEM: high resolution transmission electron microscopy; IL-1ß: interleukin-1ß; DM: dispersion medium; WLL: whole lung lavage; IL-18: interleukin-18; GSD: geometric standard deviation; XPS: X-ray photoelectron spectroscopy; SEM: standard error of the mean; PMA: phorbol 12-myristate 13-acetate; LPS: lipopolysacharride; LDH: lactate dehydrogenase; AM: alveolar macrophage; PMN: polymorphonuclear leukocyte